Convergence and Divergence among Countries - Wahiba, Nasfi Fkili (Asian Economic and Financial Review, 2015)
This paper focuses on the study of the conditional convergence hypothesis among African countries that belonging to the West African Economic and Monetary Union (WAEMU), More precisely, this paper treats even the effect of convergence, stability and growth pact on the convergence dynamics, by considering control variables comprising: the share of investment in gross domestic product the enrollment and the opening ratio, the study showed that these variables contribute to the revival of economic growth in the region. We use two estimation technique: within and system generalized method of moment, for the period 2000-2012. Similarly we give special attention to two streams of conflicting thoughts. The first is based on the positive impact generated by the opening on convergence of income among nations, while the second is almost contradictory to the one defined above, this current is called divergence or inequality between countries.